1981
DOI: 10.1063/1.92574
|View full text |Cite
|
Sign up to set email alerts
|

Chaos and noise rise in Josephson junctions

Abstract: Digital computer simultations have been used to map parameters of the transition to chaos in an rf current driven Josephson junction. Our results are qualitatively like those reported by others using analog techniques, but differ quantitatively. Our calculations show that the parameters for the onset of chaos are the same as those required for high parametric gain. This leads to the conclusion that the ’’noise rise’’ in Josephson junction parametric amplifiers is due to chaos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

1983
1983
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(20 citation statements)
references
References 3 publications
0
18
0
2
Order By: Relevance
“…It was also shown that the onset of chaos as a function of frequency correlated with the function that indicated infinite gain, also as a function of frequency, for the unbiased parametric amplifier [17]. More recently the importance of chaos in intrinsic JJs, and its effects on the IV-characteristics and the Shapiro steps in these systems, were stressed in Refs.…”
Section: Introductionmentioning
confidence: 97%
“…It was also shown that the onset of chaos as a function of frequency correlated with the function that indicated infinite gain, also as a function of frequency, for the unbiased parametric amplifier [17]. More recently the importance of chaos in intrinsic JJs, and its effects on the IV-characteristics and the Shapiro steps in these systems, were stressed in Refs.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, there are certain classes of more realistic models which share specific properties of maps such as being low-dimensional and exhibiting certain periodicities. Indeed, theoretical investigations of chaotic billiards subject to external fields [27], of periodic Lorentz gases [28,29], and of pendulum-like differential equations [30,31,32,33,34,35,36] showed that many properties of deterministic transport in maps carry over to these more complex chaotic dynamical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Each junction is characterized by an order parameter phase difference , a critical current i c , capacitance C, and normal resistance R. The junctions are biased with identical ac current sources i 0 cos t, but no dc source is included. This ac-only driving scenario is commonly adopted to probe essential chaotic behavior in Josephson systems 5,8,[11][12][13][14] and in driven pendulums. 15 The dynamical equations for the two junctions are, in this case,…”
Section: A Coupled Parallel-connected Josephson Junctionsmentioning
confidence: 99%
“…3 That is the question addressed in this paper. Thus, two phenomena which have been studied extensively but separately in connection with Josephson junctions-synchronized oscillations 4 and chaotic dynamics [5][6][7][8][9][10] -appear here in combination.…”
Section: Introductionmentioning
confidence: 99%